2017
DOI: 10.1002/celc.201700160
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Manganese Sulfide Nanostructures on Graphene as an Oxygen Reduction Catalyst for Anion Exchange Membrane Fuel Cells

Abstract: The development of active, inexpensive, and durable nonprecious-metal electrocatalysts to replace high-cost Pt-based catalysts towards the commercialization of fuel cell technology is the focus in recent years. In this regard, we report a facile one-pot hydrothermal synthesis of self-assembled manganese sulfide on graphene layers (MnS/G), and is recognized as a nonprecious-metal catalyst for the efficient oxygen reduction reaction (ORR) in an alkaline medium. The phase purity and surface morphologies are inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Moreover, the 30 nm@Fe‐N‐Csample exhibits excellent long‐term durability. As shown in Figure b, with a 0.6 V constant voltage, the output power density of the 30 nm@Fe‐N‐C sample could steadily operate for more than 60 h with only 4.65 % performance degradation, which shows substantially higher stability than commercial Pt/C with more than 18.6 % retention of its initial electrochemical activity after 60 h, which is also superior to the durability performance investigated in recent reports . The LSV curve of the 30 nm@Fe‐N‐C sample was acquired before and after 1000 cycles testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the 30 nm@Fe‐N‐Csample exhibits excellent long‐term durability. As shown in Figure b, with a 0.6 V constant voltage, the output power density of the 30 nm@Fe‐N‐C sample could steadily operate for more than 60 h with only 4.65 % performance degradation, which shows substantially higher stability than commercial Pt/C with more than 18.6 % retention of its initial electrochemical activity after 60 h, which is also superior to the durability performance investigated in recent reports . The LSV curve of the 30 nm@Fe‐N‐C sample was acquired before and after 1000 cycles testing.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6b,w ith a0 .6 Vc onstant voltage,t he output power density of the 30 nm@Fe-N-C sample could steadily operate for more than 60 hw ith only 4.65 %p erformance degradation, which shows substantially higher stability than commercial Pt/C with more than 18.6 %r etention of its initial electrochemical activitya fter 60 h, whichi sa lso superiort ot he durability performancei nvestigated in recent reports. [46,47] TheL SV curve of the 30 nm@Fe-N-C sample was acquired before anda fter 1000 cycles testing. As shown in Figure6c, the ORR onset potential and half-wavep otential did not change, which provedt hat the catalyst activity was not significantlyr educed,b ut the diffusion-limiting current of the samples decreased from 4.7 to 4.2 mA cm À2 .Chronoamperometric responses were monitored to characterize the CO tolerance of the catalysts.T he 30 nm@Fe-N-Ccatalyst shows as ignificantly better tolerance to CO than commercial Pt/C (Figure 5d), indicating that the as-obtained 30 nm@Fe-N-C catalyst holds great potential as an ultra-stable ORR catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Further, oxygen reduction reaction (ORR) is more favorable in alkaline electrolytes reducing the ORR overpotential and allowing to use lower catalyst loading contributing to reduce environmental pollution [13,14]. The other benefit of AEMFC is that alkaline cell atmosphere give raise a possibility to adopt broad category of materials as bipolar plates and other cell components [8,10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…, MoS2 etc. )[16,70,71] and carbon nanomaterials (graphene, MWCNTs and their derivatives)[40,[78][79][80][81] could be employed as electrocatalysts in AEMFC. Since none of them is really commercialized, the state of art is based on Pt supported on carbon black with an anion exchange ionomer (AEI).…”
mentioning
confidence: 99%
“…Wang et al [25] synthesized cobalt sulfide/graphene composite and have shown efficient electrocatalysis for ORR in alkaline medium. Sahu et al reported metal sulphide (Mo, Co and Mn) [26][27][28] -graphene composites as efficient ORR catalyst and evaluated their performance in AEMFCs environment.…”
Section: Introductionmentioning
confidence: 99%